Central Retinal Artery Occlusion: Current Practice, Awareness and Prehospital Delays in Switzerland - Ardila Jurado, Elena; Sturm, Veit; Brugger, Florian; Nedeltchev, Krassen; Arnold, Marcel; Bonati, Leo H.; Carrera, Emmanuel; Michel, Patrik; Cereda, Carlo W.; Bolognese, Manuel; Albert, Sylvan; Medlin, Friedrich; et al. (Frontiers in Neurology, 2022)
Background and purpose Central retinal artery occlusion (CRAO) often leads to permanent monocular blindness. Hence, early recognition and rapid re-perfusion is of paramount importance. This study aims to describe prehospital pathways in CRAO compared to stroke and study the knowledge about CRAO. Methods 1) Description of baseline characteristics, prehospital pathways/delays, and acute treatment (thrombolysis/thrombectomy vs. standard of care) of patients with CRAO and ischemic stroke registered in the Swiss Stroke Registry. 2) Online survey about CRAO knowledge amongst population, general practitioners (GPs) and ophthalmologists in Eastern Switzerland. Results 397 CRAO and 32’816 ischemic stroke cases were registered from 2014 until 2019 in 20 Stroke Centers/Units in Switzerland. In CRAO, 25.6% arrived at the hospital within 4 hours of symptom onset and had a lower rate of emergency referrals. Hence, the symptom-to-door time was significantly longer in CRAO compared to stroke (852min. vs 300min). The thrombolysis/thrombectomy rate was 13.2% in CRAO and 30.9% in stroke. 28.6% of the surveyed population recognised CRAO-symptoms, 55.4% of which would present directly to the emergency department in contrast to 90.0% with stroke symptoms. Almost 100% of the ophthalmologist and general practitioners recognised CRAO as a medical emergency and 1/3 of them considered IV thrombolysis a potentially beneficial therapy. Conclusions CRAO awareness of the general population and physician awareness about the treatment options as well as the non standardised prehospital organisation, seems to be the main reason for the prehospital delays and impedes treating CRAO patients. Educational efforts should be undertaken to improve awareness about CRAO.